Thermohaline variability of AAIW in the Atlantic sector of the Southern Ocean investigated using an Altimetry Gravest Empirical Mode - Hutchinson, Katherine Alessandra (Department of Oceanography, 2014)
The southeast Atlantic sector of the Southern Ocean connects the Atlantic with the Indian Ocean and the Antarctic Circumpolar Current, thereby acting as a major conduit within global ocean circulation. Thermohaline transports in this region are widely thought to have a critical influence on global climate. Yet magnitudes of the associated heat and salt content variations are poorly understood due to a lack of hydrographic observations and model limitations. An improved Gravest Empirical Mode (GEM) is set up for the Southern Ocean south of Africa using the updated store of hydrographic measurements obtained from CTD transects for the area, combined with the available Argo profiles sampled in the region. Satellite altimetry is combined with the GEM relationships to create an Altimetry GEM (AGEM), thereby generating 20 years of temperature and salinity fields. These thermohaline sections for the region of the ocean south of Africa are found to be proficient at reproducing observations, with associated RMS errors being two orders of magnitude smaller than those reported by other comparable Southern Ocean GEM studies. Confident in the accuracy of the AGEM produced fields, an examination of the temporal evolution of Antarctic Intermediate Water (AAIW) is undertaken. The fluctuation and trends in heat and salt content anomalies and budgets is presented for each Southern Ocean frontal zone, along with the examination of the change in position of the isopycnal limits and resultant water mass thickness. So as to better understand one of the factors that may be influencing some of the changes detected within AAIW, property alterations of eddies identified in the region from 1992 to 2010 are investigated. A general decrease in magnitude and frequency of cyclones, coupled with an increase in absolute dynamic topography (ADT) of anticyclones, designates elevated injection of warm, saline water into the area. The connection identified between eddy property variations and AAIW modification in the region of the ocean south of Africa indicates that the water mass experiences ventilation with the mixed layer at latitudes further north than previously thought to occur. Obtaining an improved image of the magnitudes and variability of AAIW thermohaline properties in the Atlantic sector of the Southern Ocean greatly improves our understanding of its role in the ocean-climate system.